The effect of topical ointment on neonatal sepsis in preterm infants. (January 2015) - Erdemir, Aydin; Kahramaner, Zelal; Yuksel, Yelda; Cosar, Hese; Turkoglu, Ebru; Sutcuoglu, Sumer; Ozer, Esra Arun; Kose, Sukran
Abstract Objective: To investigate the effects of topical ointment therapy on neonatal sepsis in premature infants. Methods: A total of 197 premature infants ≤ 34 weeks gestation were randomized to receive topical ointment (Aquaphor Original Emollient) or routine skin care group. Skin cultures were obtained on 3th, 7th and 14th day and blood cultures were obtained if sepsis was suspected clinically. Data included the maternal and neonatal characteristics, factors affecting the risk of sepsis and neonatal outcomes of both groups were collected. Results: There were no significant differences in terms of gestational age, birth weight, gender, mode of delivery, multiple pregnancy and receiving antenatal corticosteroids between the study and control group. No statistically significant difference was found in the prevalence of sepsis, in the positive skin culture rates at any follow-up and in terms of the neonatal morbidities including patent ductus arteriosus and necrotizing enterocolitis between the groups. Although the rate of death was higher in the topical ointment group, no statistically significant difference was found between the groups. Conclusions: Our data suggests that applying topical ointment during the first 2 postnatal weeks did not affect the risk of neonatal sepsis in preterm infants, although it changed the bacterial flora on the skin compare to the routine care group.